Loc’d and Faded, Yoga Pants and Spaghetti Straps: Discrimination in Dress Codes and School Pushout - Martin, Jennifer L.; Brooks, Jennifer N. (International journal of education policy and leadership, 2020)
In this paper, we review the current dress code violations that have made national news. These issues have spotlighted racist and sexist issues embedded within common K-12 dress codes. We also analyze all school dress codes within one county in a mid-western state to examine various racist and sexist issues. We end the paper with an assessment for readers to determine the levels of racism and sexism in their own K-12 district dress codes.